Sexist language among university students in Malaysia - Nur Faten Amira Phaharoradzi,; Azianura Hani Shaari, (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2021)
Traditionally, stereotype of sexism can be referred to as the beliefs people hold about members of the categories man or woman. Sexist language, on the other hand, is defined as any language that is supposed to include all people, but excludes gender. The present study, therefore, looks into some linguistic features that indicate sexism among men and women. The study aims to identify 1) the common features of sexist language recognised by university students in Malaysia, and 2)the level of awareness towards sexist language among university students in Malaysia. 70 university students were selected as sample, and data were collected using two methods: survey and semi structured interview. Both descriptive and thematic analyses were used to analysed the data. The findings indicate that majority of the participants perceive words that narrowly define women and men as normal words, without thinking much about sexist language. The participants however, were aware of the existence of sexist language but chose to accept it as part of the cultural values and norms of the society.